KAJIAN DAMPAK PERUBAHAN PENGGUNAAN LAHAN TERHADAP DEBIT ALIRAN DAS CIUJUNG - Sulaeman, Dede; Hidayat, Yayat; Rachman, Latief Mahir; Tarigan, Suria Darma (Jurusan Teknik Sipil Universitas Tadulako, 2014)
Ciujung Watershed is considered as one of major watershed in Banten Province related to floods that take place almost every year in the area. The study aims to assess landuse change and its influence on discharge. Watershed conditions such as precipitation, discharge, peak discharge, volume rate of discharge, and runoff were analyzed in two periods: 1999-2003 and 2004-2011. Landuse changes were analyzed in 8 years period (2003-2011) as well as its influence on discharge. Average annual precipitation in the period of 1999-2003 and 2004-2011 are 2370 and 2419 mm respectively. Average annual discharge in the period of 2004-2011 increased by 15% compared to the period of 1999-2003. Watershed conditions analysis indicates that Ciujung watershed quality decreased with increasing in surface runoff coefficient with values of 0.43 (period 1999-2003) and 0.48 (period 2004-2011). The study showed that there are several decreasing landuses during period 2003-2011 such as open land, natural forest, mixed dry land farming, secondary dry forest, primary dry forest, and dry land farming by 47.4; 14.3; 8.4; 2.9; 1.6 and 0.1% respectively. Several increasing land uses during the period including bush, plantations, settlements, and paddy field by 1,974.5; 5.5; 3.8 and 0.9% respectively. Keywords: discharge, land use change, peak discharge, runoff Ciujung Watershed is considered as one of major watershed in Banten Province related to floods that take place almost every year in the area. The study aims to assess landuse change and its influence on discharge. Watershed conditions such as precipitation, discharge, peak discharge, volume rate of discharge, and runoff were analyzed in two periods: 1999-2003 and 2004-2011. Landuse changes were analyzed in 8 years period (2003-2011) as well as its influence on discharge. Average annual precipitation in the period of 1999-2003 and 2004-2011 are 2370 and 2419 mm respectively. Average annual discharge in the period of 2004-2011 increased by 15% compared to the period of 1999-2003. Watershed conditions analysis indicates that Ciujung watershed quality decreased with increasing in surface runoff coefficient with values of 0.43 (period 1999-2003) and 0.48 (period 2004-2011). The study showed that there are several decreasing landuses during period 2003-2011 such as open land, natural forest, mixed dry land farming, secondary dry forest, primary dry forest, and dry land farming by 47.4; 14.3; 8.4; 2.9; 1.6 and 0.1% respectively. Several increasing land uses during the period including bush, plantations, settlements, and paddy field by 1,974.5; 5.5; 3.8 and 0.9% respectively. Keywords: discharge, land use change, peak discharge, runoff